Polymorphism in Apolipoprotein C3 (APOC3) and Fatty Acid-Binding Proteins (FABP2) Genes in Nondiabetic Dyslipidemic Patients: A Tertiary Care Hospital-Based Pilot Study - Chowdhary, Rashmi; Masarkar, Neha; Khadanga, Sagar (Journal of Laboratory Physicians, 2021)
Context Dyslipidemia is a multifactorial disease in which lipoproteins play an important role as one of the early markers for coronary heart disease (CHD). Mixed dyslipidemia is common in people with diabetes mellitus, but nondiabetic dyslipidemics (NDD) remain unidentified for the risk of developing dyslipidemia and eventually CHD.Objectives This pilot study attempts to analyze the genetic basis of lipid metabolism alterations, emphasizing the association between fatty acid-binding protein-2 (FABP2-Ala54Thr) and apolipoprotein-C3 (APOC3-rs5128) genetic polymorphism, as a risk for developing dyslipidemia and CHD in NDD.Methods and Design Total 90 subjects—30 DD, 30 NDD, and 30 apparently healthy subjects representing Central India—were included. Biochemical analysis and DNA genotyping were done by polymerase chain reaction restriction fragment length polymorphism.Statistical Analysis The biochemical parameters were reported as means ± standard deviation. One-way analysis of variance test was used to compare biochemical parameters of three groups. Chi-squared test was done to compare genotype distributions. The strength of association was assessed by odds ratios (ORs) with 95% confidence intervals (CIs). All statistical analysis was done using SPSS-PC software and Graph Pad.Results In NDD, maximum polymorphism was observed followed by DD and least polymorphism was observed in controls. There was a significant association of APOC3 G allele with occurrence of hypertriglyceridemia (p < 0.05); however, no such association was found for FABP2 A allele (p > 0.05). Logistic regression analysis revealed APOC3 polymorphism to be significantly associated with dyslipidemia (OR = 2.6667, 95% CI = 1.0510–6.7663, p = 0.0341); no such association was found for FABP2 polymorphism (OR = 0.4643, 95% CI = 0.1641–1.3136, p = 0.1347). The triglyceride and cholesterol values in individuals with homozygous genotype indicate that genetic study is comparable to the biochemical findings in carriers of polymorphic allele than noncarriers, especially in NDD patients.Conclusions Pilot study indicates that the presence of APOC3 gene polymorphism is associated with pro-atherogenic dyslipidemia in nondiabetic patients and may raise risk of CHD. This information could be used for preventive strategies in NDD group that may otherwise go unnoticed.
Keywords: APOC3; dyslipidemia; FABP2; nondiabetic; polymorphism